ANALYSIS OF PEMANGKU AND PENGAYAH BLOOD GLUCOSE LEVELS AT BESAKIH TEMPLE - Dwijastuti, Ni Made Sri; Septiasari, Ni Putu Senshi; Dewi, I Gusti Agung Ayu Satwikha; Widiantari, Ni Putu; Putri, Ni Putu Puniari Eka (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Background: Every year on Sasih Kedasa, Besakih Temple holds a series of ceremonies called Ida Bhatara Turun Kabeh. The ceremony is held annually for approximately one and a half months. The workload of Pemangku and Pengayah during the ceremony, with a long duration and repetitiveness, is considered to cause physical fatigue, which leads to increased stress and an increased tendency to eat poorly. Pemangku and Pengayah are also vulnerable to sunburn, coffee, sleep loss, and dehydration while on duty. These factors trigger diabetes and spikes in blood glucose levels (BGL). Aims: To analyze the BGL of Pemangku and Pengayah in Besakih temple. Methods: It is observational research with a cross-sectional approach. Data collection was carried out by Point of Care Testing (POCT), supported by interviews with 66 respondents to determine individual conditions. The results: One of the adult female respondents shows low BGL (48 mg/dl). High BGL (335,2 mg/dl on average) was obtained from five respondents: adult women, older women, and three elderly men. The rest of the respondents show normal BGL, which is 125,6 mg/dl on average. Conclusions: As many as 1,5% had low, 7,6% had high, and 90,9 % had normal BGL of 66 Pemangku and Pengayah at Besakih Temple.